Assessment of School Improvement Plan 2013-2015: Basis for the Technical Assistance Plan (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aimed to determine the level of assessment of School Improvement Plan 2013-2015: basis for the Technical Assistance Plan in the Division of Sagay City, Negros Occidental. The respondents of the study were the 72 school heads, 72 teachers-representatives who were member of the school planning team, 72 parents and 25 LGU representatives in the Division of Sagay City. The validated instruments were distributed and discussed during the Focus Group Discussion to the four group of respondents. The study employed the descriptive research design. The processing of data was done with the use of Statistical Package for Social Sciences (SPSS) Software.The mean was used to determine the level of assessment of the four groups of respondents in the three phases and when they are grouped according to their profile variables. Mann-Whitney U-Test was used to determine whether or not significant difference existed on the level of assessment of school improvement plan in the three phases when the four group of respondents were grouped and compared according to their profile variables. Qualitative questions were classified, grouped and synthesized based on the magnitude of observation for intervention. Results of the study showed that the level of assessment of the school heads revealed a very high rating in the Assess, Plan and Act phases and when taken as a whole. Teachers rated the three phases in a high level. Parents rated the Assess phase in a high level, while Plan and Act phases in a moderate level. Likewise, LGU representatives rates the Assess phase in a very high level, Plan phase as high level and the Act phase as moderate level. When differences were considered school heads, parents and LGU representatives find no significant difference on the level of assessment on school improvement plan. Teachers revealed a significant difference in the Assess phase when grouped and compared according to position title. For the Plan phase, a significant difference found when grouped according to highest educational attainment, position title and average family monthly income. Further, for Act phase, a significant difference existed when grouped according to age. The rest of the responses find no significant difference. Examining deeper the results of the study reveals that it is essential for DepEd Division of Sagay City to package technical assistance plan for the four respondents on various issues contributory to the crafting of School Improvement Plan.